Inter-regional patterns of life span in Pakistan: a life table analysis. (2017) - Shahzad, Faisal; Nasir, Jamal Abdul; Ali, Asif; Soomro, Munawar Hussain
A set of life tables for seven geographic regions of Pakistan is presented. Data from Pakistan Demographic Survey – 2007 is used for the preparation of life tables. Life expectancy at birth for male is found 64.21 year in the province of Punjab, shows the highest one and 54 years for female found in the Baluchistan province which is least one. Further, urban areas of Pakistan have been seen on the forefront in terms of life expectancy in Pakistan. From the life table analysis a substantial sex differential could be discerned. The pattern of life expectancy in Baluchistan province is interesting to note, males are having higher life expectancy as compared to females.